Analisis Variasi Rapat Dan Tegangan Pada Proses Anodisasi Terhadap Kekerasan dan Ketahanan Aus Paduan Aluminium - Muhammad Adrian Rizky; Nani Mulyaningsih; Fendy Kussuma Hadi Sufyan (CV. IRA PUBLISHING, 2025)
Aluminum alloys are widely used in the automotive industry, particularly for radiators, due to their lightweight nature, good corrosion resistance, and excellent thermal conductivity. However, these materials remain vulnerable to wear from internal erosion and contamination, necessitating additional protection. This study investigates the effects of varying current density and voltage during anodizing on the hardness and wear resistance of 3xxx-series aluminum alloys. The process was carried out in a sulfuric acid (H₂SO₄) electrolyte for 40 minutes using currents of 4 A and 5 A, combined with voltages of 25 V and 35 V. Micro-Vickers testing revealed the highest hardness of 162.63 VHN at 4 A and 25 V, while the best wear resistance was achieved at 5 A and 35 V with a specific wear rate of 0.000302371 mm³/kg (an improvement of 24%).